2022
DOI: 10.1016/j.enfcle.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prenatal stress and anxiety in pregnant women during COVID-19 in Spain

Abstract: Aim of the study To describe prenatal stress and state anxiety levels in pregnant women living in Spain during the lockdown of the first wave of COVID-19 and its relation with obstetric factors, perception of health care, and concerns about the socio-sanitary situation. Methods The present study is an observational, correlational, and cross-sectional quantitative study. The participants in the study were pregnant women recruited through non-probabilistic convenience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(32 reference statements)
4
8
0
1
Order By: Relevance
“…Furthermore, the result of the study showed that nearly a third of pregnant women experienced elevated stress levels related to feeling unprepared for birth or being worried about perinatal infection. The result is similar to a previous study (Sirhan et al, 2022) which recorded that the COVID-19 pandemic was associated with high-stress levels and mental health problems. Biresaw et al (2022) wrote that a recent study during the COVID-19 pandemic period indicated that there is increased anxiety and poor quality of sleep levels.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the result of the study showed that nearly a third of pregnant women experienced elevated stress levels related to feeling unprepared for birth or being worried about perinatal infection. The result is similar to a previous study (Sirhan et al, 2022) which recorded that the COVID-19 pandemic was associated with high-stress levels and mental health problems. Biresaw et al (2022) wrote that a recent study during the COVID-19 pandemic period indicated that there is increased anxiety and poor quality of sleep levels.…”
Section: Discussionsupporting
confidence: 91%
“…Findings indicate that greater negative COVID impact, lower education, and lower social support were positively associated with higher levels of distress levels during pregnancy. These findings are in line with prior research indicating that social support is a protective factor (e.g., Lebel et al, 2020;Zhou et al, 2021;Khoury et al, 2021b;Fernandes et al, 2022) and COVID-related stress is a risk factor (e.g., Khoury et al, 2021b;Awad-Sirhan et al, 2022;Giesbrecht et al, 2022) for mental health and distress in prenatal and postpartum samples during the pandemic. In particular, prior work by Fernandes et al (2022) showed that higher social support was associated with lower levels of depression from pregnancy 6-months postpartum.…”
Section: Factors Related To Distress: Education Level Covid Impact An...supporting
confidence: 91%
“…Significant higher levels of PDQ were observed in Group 1: pregnant women recruited face-to-face in health centres during Spain´s severest restrictions on individual mobility and highest psychological uncertainty. There is evidence that the pandemic has impacted the general population’ s level of anxiety, specifically among pregnant women, who reported anxiety levels about two-thirds higher than normal [ 14 , 15 , 25 , 43 ]. We observe that visiting the health centre at a time of greatest threat and uncertainty may trigger high stress levels and concerns about being exposed to the Coronavirus in the hospital environment, as evidenced in Group 1 results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of prenatal stress and associated risk factors is more dramatic in an exceptional situation such as a pandemic. There is evidence that the pandemic has amplified the general population’s levels of anxiety and depression, and other psychiatric conditions, specifically among pregnant women [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%